A critical review to determine what new and evolving Trauma Systems in England can learn from their mature and established counterparts overseas. - Corbett, Imogen (2012)
Background: Trauma care in England is below the standards of service provision when compared to many other developed countries. In recent years there has been an impetus for improvements in trauma care and as a result, Trauma Systems are beginning to roll out across England to meet the complex needs of trauma patients and bring the quality of service provision into line with international comparators. Aim: This review aims to explore the extent to which, new and evolving Trauma Systems in England, can learn and implement ideas from their mature and established counterparts overseas to deliver high quality trauma care to severely injured patients. Methods: A critical review of the literature has been undertaken and an analytical framework has been developed to explore and assess the components of an effective Trauma System. Findings: After reviewing the literature on Trauma Systems focussing on topics of patient outcomes, business case and nursing, it was found that systematic improvements in trauma care occur over time with improvements in system organisation and structure. Further improvements in Trauma Systems can come from comprehensive treatment of all triage positive patients within the Trauma System, additional data collection addressing trauma morbidities and patient quality of life, service and system evaluation to identify and address inadequacies, rehabilitation improvements and long term patient follow up, trauma prevention strategies and facilitation of nurse empowerment and professional development. Conclusion: The 2012 Framework for Trauma Systems has been developed and used as an analytical tool to identify the components of an effective Trauma System. It should be adopted when implementing and assessing effective trauma systems to ensure that all patient and system needs are addressed. A critical P a g e | vii review of the literature has been conducted and recommendations for effective trauma system implementation in England have been made.